Menilai Kualitas Hidup Anak Penyandang Hemofilia - Shanessa Budiarty; Selvi Nafianti (PT. Kalbe Farma Tbk., 2020)
Hemofilia merupakan penyakit congenital defisiensi faktor koagulasi dengan manifestasi perdarahan. Hemofilia dapat mengganggu kualitas hidup fisik, sosial, sekolah dan emosi penyandangnya. Salah satu instrumen untuk menilai kualitas hidup anak adalah pediatric quality of life questionnaire/PedsQL; penggunaannya di kalangan penyandang hemofilia anak dapat menunjang tatalaksana.Hemophilia is a congenital coagulation deficiency associated with bleeding manifestation. Hemophilia can affect physical, social, school and emotional quality of life; children with hemophilia can have lower self perception compared to healthy children. Pediatric quality of questionnaire/PedsQL is an instrument for assessment of quality of life in children; it use among children with hemophilia can improve their management.